THE IMPORTANCE OF FOREIGN INVESTMENTS IN THE ECONOMIC DEVELOPMENT OF THE COUNTRY - Kurganov Hakimjon Rustamovich; Abdurahmanova Zulayho Olimzhanovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Stable socio-economic development of the Republic of Uzbekistan and growth of global competitiveness cannot be achieved without an effective investment policy of the state aimed at increasing the attractiveness of the investment environment of the country, regions, economic sectors and individual enterprises. It is known from world practice that any country cannot develop without attracting foreign investments to its economy. Development of production, renewal of basic funds, elimination of social problems, increase of competitiveness of products produced on the basis of modern techniques and technologies, and strengthening of export potential of the country are ensured through investments. The main factor in the consistent implementation of structural changes in Uzbekistan is the attraction of foreign investments to our economy and the creation of a favorable investment environment for them. In this article, a set of economic, political, regulatory, social and other conditions plays a key role in attracting foreign investments. Such opportunities include natural conditions, including mineral reserves, the level of skill and average labor force, the capacity of the domestic market and the ability to sell goods on the foreign market, the state of the credit system, the level of taxation, production and social infrastructure. development, the state policy towards foreign capital, the establishment of preferential conditions for it, etc.